2017
DOI: 10.1111/1475-6773.12759
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Receipt of Influenza and Pneumococcal Vaccination among Long‐Stay Nursing Home Residents

Abstract: Racial/ethnic differences remain despite policy changes. Focused strategies aimed at NH personnel and racially segregated NHs are critical to improving vaccination delivery and eliminating disparities in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…17 Similar to prior research, we categorized proportions of Black residents in nursing homes as none, <20%, 20%e49.9%, !50%, or not reported. 3,18 We combined the 50%e79.9% group (n ¼ 558), 80%e 94.9% group (n ¼ 109), and the 95%e100% group (n ¼ 14) to provide sufficient power. Not reported denotes nursing homes that had missing data for their percentage of racial/ethnic minorities.…”
Section: Methodsmentioning
confidence: 99%
“…17 Similar to prior research, we categorized proportions of Black residents in nursing homes as none, <20%, 20%e49.9%, !50%, or not reported. 3,18 We combined the 50%e79.9% group (n ¼ 558), 80%e 94.9% group (n ¼ 109), and the 95%e100% group (n ¼ 14) to provide sufficient power. Not reported denotes nursing homes that had missing data for their percentage of racial/ethnic minorities.…”
Section: Methodsmentioning
confidence: 99%
“…My study suggests there is something specific about heterosexuality in combination with black identity is driving lower vaccination. As previously discussed, black adults face many barriers to vaccinate against influenza, such as not being offered the vaccine (Travers et al, ( 2018 ) denying the vaccine due to mistrust and lower vaccine literacy (Chen et al, 2007 ; Quinn et al, 2016 ; Quinn et al, 2017 ; Quinn, 2018 ), and, in general, a lack of access to healthcare and quality healthcare due to racism (Phelan & Link, 2015 ). Research has also found higher proportions of racial consciousness led to lower vaccination rates among black adults (Quinn et al, 2017 ) and general worry about adverse effects of the vaccine (Freimuth et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, vaccination is the most effective strategy to reduce influenza death and illness, with vaccination being recommended for anyone over 6 months of age to prevent disease among individuals and their communities (CDC, 2021a(CDC, , 2021b(CDC, , 2021cUS Department of Health & Human Services, 2022). Studies often focus on vaccination among elderly and/ or high-risk individuals, rather than larger population-based samples (e.g., Travers et al, 2018). Scholarship using National Health Interview Survey (NHIS) found in 2015-2016, influenza vaccination had increased among adults aged 18-64 (at 1.5%, on average, each year) compared to 2010-2011 (Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While it is often difficult to assess the complex psychological, sociological, and demographic factors (Travers, Dick, & Stone, 2018 ) associated with healthcare choices, and in particular, the choice to get vaccinated, the results of this work help shine a light on some important points of engagement policymakers have with individuals who have not vaccinated in the past. For example, if the problem is that individuals who are more risk-tolerant are also more likely to refuse the seasonal influenza vaccination, which is consistent with my findings, targeted campaigns for this group may tip the balance in favour of getting protection.…”
Section: Discussionmentioning
confidence: 99%